Bureaucratic Contestation in the Resolution of Divorce Cases Among the Muslim Community in Langsa City, Aceh - Muhazir Muhazir; Muhammad Syukri Albani Nasution; Arifuddin Muda Harahap (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The issue of divorce in Aceh is multifaceted, encompassing the interplay between customary law and the Sharia Court in resolving family disputes. While Indonesian national law governs divorce through formal judicial proceedings, many in Aceh opt for settling divorces through customary institutions aligned with Islamic values. This study aims to examine the role of these customary institutions in divorce resolution within Langsa City, Aceh, and to explore the factors influencing the community's choice of either customary law, the Sharia Court, or both. The research adopts a juridical-empirical approach with a legal pluralism framework, combining an analysis of formal legal structures with the practical legal realities in local communities. Data was collected through in-depth interviews with local residents, religious figures, and leaders of customary institutions in Langsa. The results reveal a clear tension between customary practices and the national legal system in divorce matters, with a significant portion of the population preferring customary procedures due to their accessibility and greater social acceptance. However, such customary decisions lack formal legal recognition, leading to uncertainty regarding the post-divorce rights of women and children. This study offers valuable insights into the evolving divorce practices in Aceh, shedding light on the intersection of customary law, Sharia law, and national legislation. It also suggests that greater integration of these legal systems is necessary to ensure a more just and transparent process for divorce resolution in the region.